Livestock Health and Farming 2020
DOI: 10.5772/intechopen.90109
|View full text |Cite
|
Sign up to set email alerts
|

Livestock Feeds and Feeding in Semi-Arid Areas of Southern Africa

Abstract: Livestock production is the major source of rural livelihoods in semi-arid regions of Southern Africa. However, nutrition is the major limiting factor of livestock production in these areas characterised by declines in rangeland productivity due to the increases in drought frequency, deliberate overstocking by farmers, and climate change and variability. For instance, the grazing resource is strongly influenced by seasonality of rainfall. Poor-quality cereal crop residues are the main dry season supplementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…This explains the high adoption of these species by livestock farmers in Kajiado County. The current study findings are also corroborated by Mudzengi et al (2020) who indicated that indigenous browse species such as Acacia remain a significant source of abundant and persistent animal feeds in arid and semi-arid areas, especially during drought.…”
Section: Improved Livestock and Napier Grass Breedssupporting
confidence: 87%
“…This explains the high adoption of these species by livestock farmers in Kajiado County. The current study findings are also corroborated by Mudzengi et al (2020) who indicated that indigenous browse species such as Acacia remain a significant source of abundant and persistent animal feeds in arid and semi-arid areas, especially during drought.…”
Section: Improved Livestock and Napier Grass Breedssupporting
confidence: 87%
“…In semi-arid regions, the dry season is a major obstacle to animal production due to food shortages and reduced nutritional value of available pastures (1) . Caatinga is an important food source for ruminant herds in the semi-arid regions of Brazil (2) .…”
Section: Introductionmentioning
confidence: 99%